CHALLENGES AND SOLUTIONS OF UZBEKISTAN'S TRANSITION TO MARKET ECONOMY - Xoliyarova Muxlisabonu Abduraxmonovna; Sayfullayeva Nigora Fayzulla qizi; Toshtemirova Muhlisa Davronbek qizi; Shokirov Humoyiddin Baxriddin o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the system of market economy and its implications in detail. Show the shortcomings in the relationship between the seller and the buyer in the market .And a comprehensive solution has been found to these shortcomings.